2016
DOI: 10.7717/peerj.2115
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cost-effective metabarcoding strategy for analysis of the marine phytoplankton community

Abstract: We developed a cost-effective metabarcoding strategy to analyze phytoplankton community structure using the Illumina MiSeq system. The amplicons (404–411 bp) obtained by end-pairing of two reads were sufficiently long to distinguish algal species and provided barcode data equivalent to those generated with the Roche 454 system, but at less than 1/20th of the cost. The original universal primer sequences targeting the 23S rDNA region and the PCR strategy were both modified, and this resulted in higher numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Thus, currently, some universal metabarcoding assays result in low taxonomic resolution. OTU analyses, which make up the bulk of eDNA metabarcoding research to date, have been proposed to alleviate some of the problems associated with universal primer sets (Yoon et al, ). However, OTU metrics are known to inflate biodiversity estimates (Diaz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, currently, some universal metabarcoding assays result in low taxonomic resolution. OTU analyses, which make up the bulk of eDNA metabarcoding research to date, have been proposed to alleviate some of the problems associated with universal primer sets (Yoon et al, ). However, OTU metrics are known to inflate biodiversity estimates (Diaz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al. () recently provided modifications to the UPA primers and cycling conditions that resulted in a substantial decrease in the proportion of heterotrophic bacterial reads obtained in an Illumina metabarcoding study of marine phytoplankton, which holds promise for increasing the efficiency of future NGS applications of this marker. Sauvage et al.…”
Section: Discussionmentioning
confidence: 99%
“…In our results here, we recovered a large fraction of heterotrophic bacterial OTUs (33.3% of total). Yoon et al (2016) recently provided modifications to the UPA primers and cycling conditions that resulted in a substantial decrease in the proportion of heterotrophic bacterial reads obtained in an Illumina metabarcoding study of marine phytoplankton, which holds promise for increasing the efficiency of future NGS applications of this marker. Sauvage et al (2016) recently demonstrated that the tufA plastid marker can be amplified and sequenced with the Illumina platform for both cyanobacteria and eukaryotic algae in marine systems, although this marker is also unable to amplify cladophoralean taxa and may pose additional problems in amplifying trentepohlialean taxa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations